IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA MELALUI PENGENALAN KEARIFAN LOKAL TOKOH SAMIN DI TK AISYIYAH 1 BLORA - Irchamni, Achmad (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
The Project for Strengthening the Profile of Pancasila Students at Kindergarten Aisyiyah 1 Blora has only been carried out from the 2023/2024 academic year until now. The project activities that will be presented are highlighting local figures on the topic of local wisdom through the introduction of figures, the introduction of noble values, the introduction of clothes, and the introduction of the Samin pavilion which is adapted to the development stages of PAUD children. The aim of implementing the Project for Strengthening the Profile of Pancasila Students is to achieve the dimensions of Pancasila Students, where the dimensions that have been agreed by all school members to be achieved through this project are faith, devotion to the Almighty God and noble character, global diversity, working together. , independent, critical and creative reasoning. The selection to introduce the local figure Samin aims to be an effort for students to play a role in efforts to preserve local wisdom in Blora. The research method used is qualitative research where data is obtained from observation, interviews and documentation and concluded through qualitative descriptions. Through the implementation of the Project for Strengthening the Pancasila Student Profile at Kindergarten Aisyiyah 1 Blora, it is hoped that we will continue to introduce the character of Samin and his noble values that can be applied in learning activities and become a person who reflects the Pancasila Student Profile